Proceedings of the 2014 Conference on Designing Interactive Systems 2014
DOI: 10.1145/2598510.2598602
|View full text |Cite
|
Sign up to set email alerts
|

Human actions made tangible

Abstract: With designers increasingly moving beyond button pushing and flat-screen interaction towards tangible and embodied interaction, techniques for user studies need to develop as well. While ethnographic video studies and ethnomethodological analyses are becoming standard in many interaction design projects, it remains a challenge to investigate in detail how people interact with all of their body. Analysis of fullbody movement is time consuming, notation techniques are rare, and findings are difficult to share be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…To aid the design of these information driven and more continuously improved systems there is a need for efficient validation of usefulness and stakeholder acceptance. Buur et al observed, doing user studies of forklift operators, that the skilled operators perform many operations in parallel, as well as, tasks far beyond the everyday notion of 'lifting', 'carrying' and 'dropping' a load [36]. The knowledge must therefore be based system use and adoption "in the wild", thus giving a true understanding of use to complement laboratory tests and prior assumptions [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…To aid the design of these information driven and more continuously improved systems there is a need for efficient validation of usefulness and stakeholder acceptance. Buur et al observed, doing user studies of forklift operators, that the skilled operators perform many operations in parallel, as well as, tasks far beyond the everyday notion of 'lifting', 'carrying' and 'dropping' a load [36]. The knowledge must therefore be based system use and adoption "in the wild", thus giving a true understanding of use to complement laboratory tests and prior assumptions [37,38].…”
Section: Discussionmentioning
confidence: 99%